ANALISIS STUDI KOMPARASI PENYELENGGARAAN INOVASI PELAYANAN PUBLIK DI ERA NEW NORMAL - Muhammad Eko Atmojo; Helen Dian Fridayani; Vindhi Putri Pratiwi (Jurnal Transformasi Administrasi, 2021)
Public services are the face of a bureaucracy or organization, besides that, public services must also be followed by the latest innovations so that the work pattern of the bureaucracy can be easier and more transparent. Problems since the COVID-19 pandemic, public sector services have encountered extraordinary obstacles, so there must be innovations provided by the government to facilitate and accelerate the implementation of services to the community. In the era of the pandemic and the new normal, there are many city district governments that make the latest innovations to provide the best service for the community, including in Jakarta, Bandung, Semarang, Yogyakarta and Surabaya. These cities also received awards from the ministry with various awards from the innovation sector. The purpose of this study is to analyse a comparative study on the implementation of public service innovations in the new normal era. This research was conducted using qualitative methods and using research tools to process secondary data. The tool used in this study is Nvivo 12+, the data taken in this study is the processed result of data taken through online media in the five cities. Based on the results of the study, it can be concluded that many public service innovations have been formed in the five cities. As for how to measure innovation in the five cities using public service indicators, including providing solutions, compatibility, usefulness, sustainability, novelty, can be operated. From the results of data processing carried out, especially based on the indicators of public services used, the principle of providing solutions and benefits becomes the indicator with the highest assessment for each city. So, it can be concluded that the public services provided during the pandemic are very useful and on target. Suggestions and recommendations from the results of this study are the need for a change in the stigma for public service providers so that they can adapt quickly to the dynamics of changing conditions.